Postsplenectomy Kawasaki disease in a 17-year‑old male - Gharebaghi N; Aghdashi M; Seyed Mokhtari SA (International Medical Case Reports Journal, 2018)
Naser Gharebaghi,1 Miramir Aghdashi,2 Seyed Arman Seyed Mokhtari3 1Department of Infectious Disease, Faculty of Medicine, Urmia University of Medical Science, Urmia, Iran; 2Department of Rheumatology and Internal Medicine, Faculty of Medicine, Urmia University of Medical Science, Urmia, Iran; 3Student Research Committee, Urmia University of Medical Sciences, Urmia, Iran Abstract: Kawasaki disease (KD) is characterized with an acute systemic vasculitis of the medium- and small-sized vessels. This disease mainly involves children within the age of 6 months to 5 years and it is often self-limited and patients seem to recover well; however, it may lead to devastating and fatal cardiovascular complications such as coronary artery aneurysm. Thus, early diagnosis and appropriate management of this disease have a significant effect on improving the prognosis and preventing its serious complications. Adult-onset KD (AKD) is rare and often misdiagnosed. Here we report a rare case of KD that occurred in a 17-year-old young adult who presented 4 weeks post splenectomy, with clinical signs and symptoms consistent with AKD. This may potentially highlight the association of AKD with infectious etiologies. Keywords: Kawasaki disease, adult, splenectomy